Artist Statements. Issue 1 (1st June 2012) - Battey, Bret; Belantara, Amanda; Bergeron, Jason; Laliberté, Emily; Boland, Kieran; Boynton, Neil; Rose, Emma; Copps, Will; Crilly, Chris; Davies, Nance; Drivas, George; Economou, Yiannos; et al.
Sinus AestumEars are Dazzled, Touched by SoundAmongst a Sea of Scratched OrientRun it by me FirstThresholdAwakeningThe Fast RunnerTrainspositionEmpirical DataFear is a Man's Best FriendBergTerrifying BlanknessPatahV O Y A G EAppassionataPlato's PlatesThe future of music?Lines & SpacesThere are Ghosts100% Shredded WheatF-L-A-M-M-A-R-I-O-NAbiogenesisPieces of JonestownDrip WalkThe Difference MachineReterocognitionLiquid AmberBeatMagnetic Resonance MedleyEven if we think we know thingsI.will.know.youGreen Becomes Black and Blue, SmokestackA Fish's Tale